Septic Pulmonary Emboli and Renal Abscess Caused by Staphylococcus aureus in an HIV-Infected Patient - Isaí Medina-Piñón; Alan Ledif Reyes-Mondragón; Michel Fernando Martínez-Reséndez; Adrián Camacho-Ortiz (Case Reports in Infectious Diseases)
Staphylococcus aureus is a common cause of bacteremia in the general population and can lead to serious metastatic infection particularly in immunocompromised persons. However, prompt diagnosis and management can result in favorable outcomes. In the following case report, the clinical course of an HIV-infected man is presented; he developed bloodstream infection (BSI) and associated complications: septic pulmonary embolism, right renal abscess, and ipsilateral renal vein thrombosis. Methicillin-resistant Staphylococcus aureus (MRSA) was identified as the cause of sepsis and successfully treated with surgery and antimicrobials. Intravenous vancomycin was the primary therapy, followed by oral linezolid after resolution of bacteremia.